2003
DOI: 10.1002/ajh.10389
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rupture of the spleen in AL amyloidosis

Abstract: The frequency of splenic involvement in AL amyloidosis is not precisely known. However, splenomegaly has been reported in 4-13% of patients. We report four cases of spontaneous splenic rupture in patients with AL amyloidosis. Splenic rupture was the initial manifestation of the disease in one of these patients. The other three experienced splenic rupture during or after high-dose intravenous melphalan with autologous peripheral blood stem cell transplantation (HDM/SCT): one during stem cell mobilization with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 32 publications
0
51
0
Order By: Relevance
“…7 Splenic rupture during stem cell mobilization in the presence of splenic amyloidosis has been reported. 8 Investigators at Boston University reported two patients in whom splenic rupture developed because of growth factor administration. Presumably, the patients had extensive amyloid deposits in the spleen, rendering the capsule rigid during the expansion of neutrophils after filgrastim therapy.…”
Section: Introductionmentioning
confidence: 99%
“…7 Splenic rupture during stem cell mobilization in the presence of splenic amyloidosis has been reported. 8 Investigators at Boston University reported two patients in whom splenic rupture developed because of growth factor administration. Presumably, the patients had extensive amyloid deposits in the spleen, rendering the capsule rigid during the expansion of neutrophils after filgrastim therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, Oran et al [24] reported 4 cases of splenic rupture in AL amyloidosis in this journal. Three of these cases were complicated by splenic rupture during or after treatment with HDM/ASCT.…”
Section: Primary Amyloidosismentioning
confidence: 85%
“…A rare phenomenon associated with high mortality, spontaneous rupture of the spleen can occur in AL amyloidosis because of splenic enlargement, increased rigidity, amyloid angiopathy, and clotting factor deficiency. Preservation of the spleen is usually not possible in such cases [23,24]. G-CSF used during high dose Melphalan chemotherapy and autologous stem cell transplantation (HDM/ASCT) has also been implicated in causing the rupture of this friable organ, possibly by continuous proliferation of the stimulated hemopoietic stem cells [24].…”
Section: Primary Amyloidosismentioning
confidence: 99%
See 2 more Smart Citations